2010
DOI: 10.4049/jimmunol.1001222
|View full text |Cite
|
Sign up to set email alerts
|

TCR Repertoire, Clonal Dominance, and Pulmonary Trafficking of Mycobacterium-Specific CD4+ and CD8+ T Effector Cells in Immunity Against Tuberculosis

Abstract: Clonal responses of Mycobacterium tuberculosis-specific CD4+ or CD8+ T effector cells producing antituberculosis cytokine IFN-γ in the context of immune protection against tuberculosis remain poorly characterized in humans. Utilizing decade-long TCR expertise, we previously developed a useful method to isolate clonotypic TCR sequences from Ag-specific IFN-γ–producing T cells and to specifically measure clonotypic TCR frequencies in the T cell pool. In this study, we investigated TCR Vβ repertoires/CDR3 usage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…In fact, frequencies of pulmonary CD4+ and CD8+ Th1-like cells in Picostim/IL2 group are significantly higher than those in saline/BSA or IL2 alone control during primary Mtb infection. The reason why enhanced responses were seen prominent only in pulmonary compartment but not in blood may be due to the fact that pulmonary Mtb infection leads to dominance of immune responses in lung but not in peripheral blood [40]. These results suggest that phosphoantigen expansion of Vγ2Vδ2 T effector cells may serve as immune adjuvant enhancing CD4+ and CD8+ Th1 responses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, frequencies of pulmonary CD4+ and CD8+ Th1-like cells in Picostim/IL2 group are significantly higher than those in saline/BSA or IL2 alone control during primary Mtb infection. The reason why enhanced responses were seen prominent only in pulmonary compartment but not in blood may be due to the fact that pulmonary Mtb infection leads to dominance of immune responses in lung but not in peripheral blood [40]. These results suggest that phosphoantigen expansion of Vγ2Vδ2 T effector cells may serve as immune adjuvant enhancing CD4+ and CD8+ Th1 responses.…”
Section: Discussionmentioning
confidence: 90%
“…Shown on left are real time quantitative PCR data for mRNA expression levels of perforin and granulysin expressed by macaque Vγ2Vδ2 T effector cells capable of restricting intracellular Mtb growth. The quantitation was done using the methods as we previously described [40]. Data are means with SEM from phosphoantigen-activated Vγ2Vδ2 T effector cells from 3 Mtb-infected macaques in 2 independent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we are far from being able to test such hypotheses, new studies highlight the value of studying TCRs used by M. tuberculosis specific T cells. Du et al identified TCRβ sequences from PPD-reactive CD4 + and CD8 + T cells from BCG vaccinated macaques [61]. While these sequences were diverse, when challenged with M. tuberculosis , several but not all TCRβs underwent dramatic clonal expansion.…”
Section: Integration Of Multiple Signals During T Cell Priming Detmentioning
confidence: 99%
“…IFNγ has been shown to play a role in protection against active Mtb infection in mice [5]. While human studies have not found a correlation between blood IFNγ and protection against TB, our recent mechanistic studies suggest that rapid pulmonary trafficking of mycobacterium-specific CD4+ and CD8+ T effector cells producing IFNγ appears to be one of the mechanisms underlying BCG vaccine-induced immunity against primary TB [9].…”
Section: Discussionmentioning
confidence: 70%